Generation and characterization of monoclonal antibodies specific to Coenzyme A - Malanchuk, O.M.; Panasyuk, G.G.; Serbyn, N.M.; Gout, I.T.; Filonenko, V.V. (Вiopolymers and Cell, 2015)
im. Generation of monoclonal antibodies specific to Coenzyme A. Methods. Hybridoma technique. KLH carrier protein conjugated with CoA was used for immunization. Screening of positive clones was performed with BSA conjugated to CoA. Results. Monoclonal antibody that specifically recognizes CoA and CoA derivatives, but not its precursors ATP and cysteine has been generated. Conclusion. In this study, we describe for the first time the production and characterization of monoclonal antibodies against CoA. The monoclonal antibody 1F10 was shown to recognize specifically CoA in Western blotting, ELISA and immunoprecipitation. These properties make this antiboby a particularly valuable reagent for elucidating CoA function in health and disease.